Webometric Analysis of Websites of Digital Repositories of Agricultural Sciences in Asia on a Global Scale: An Overview - Ghosh, Sanjib; Roy, Bijan Kumar (Journal of Agricultural Extension Management, 2021)
This study investigates 88 open-access digital repositories of agricultural sciences in Asia. The webometric methods are used to assess the web performance of these repositories as represented by worldwide visibility and highlights the diverse link architectures and online presence using webometric indicators via the Google search engine. According to the results, the Fundamental Science Library of the NAS, Armenia is ranked first with 391000 web pages, 149000000 In-Link web pages, and 381.0741688 RWIF. Regarding the WISER index value of IDR websites, Taiwan Agricultural Research Institution occupied the first rank with 20.56, followed by the Science and Technology Development Center of the Ministry of Education of the People's Republic of China and the Tea Research Institute Repository, Sri Lanka. This study also shows a comparative study between IDRs regarding their Application Data Management values and mapping these IDS with a WebCrawler, i.e., SocScibot4. As a result of this study, information professionals, researchers, and students will better understand the high-quality websites of agricultural repositories in Asia that meet their information demands.